Model Simulasi untuk Sistem Manufaktur Fleksibel - Pakpahan, Eka Kurnia Asih; Kristina, Sonna; Setiawan, Ari (Yayasan Petra Harapan Bangsa, 2018)
This paper discussed the design of simulation model for a specific flexible manufacturing system (FMS) workstation. It consist of four CNC machines with identical processing capability, a stacker crane as material handling equipment, pallet stocker as material storage location and a computer centre as integrator of all workstation’s elements. Jobs to be processed are multi-stages which are divided by setup activity. A certain stage must be allocated on a single machine to avoid damage due to frequent material handling. Each stage consists of several operations and each operation requires a specific cutting tool. Thus, the capability of a particular machine to process a certain stage will depend on its cutting tools availability. When jobs-machine allocation has been created, it will guide the movement of material handling equipment to conduct material pickup and delivery. In this setting, the material handling equipment will perform as a shared resource, accommodating the movement of multiple jobs. By designing simulation model, this research is aimed to help production planner on determining three important decisions in timely fashion; the job-machine allocation, the number of cutting tools to be prepared on each machine’s tools magazine and the priority rule for guiding material handling equipment.Artikel ini membahas mengenai perancangan model simulasi untuk stasiun kerja di sebuah sistem manufaktur fleksibel (flexible manufacturing system/FMS). Stasiun kerja ini terdiri dari empat mesin CNC dengan kemampuan pemrosesan yang identik, sebuah alat pemindah material (stacker crane), lokasi penyimpanan material (pallet stocker) dan sebuah komputer yang mengintegrasikan semua komponen yang telah disebutkan sebelumnya. Pekerjaan yang dikerjakan di stasiun kerja ini bersifat multi-stage, setiap stage dipisahkan dengan kebutuhan setup. Sebuah stage pekerjaan harus dialokasikan ke satu mesin untuk menghindari kerusakan akibat pemindahan. Setiap stage pekerjaan terdiri dari beberapa operasi, dimana setiap operasi membutuhkan perkakas potong khusus. Untuk itu, mampu atau tidaknya sebuah mesin memproses sebuah stage pekerjaan ditentukan oleh ketersediaan perkakas potong yang dibutuhkan oleh rangkaian operasi dalam stage tertentu pada mesin tersebut. Saat alokasi pekerjaan ke mesin sudah dibuat, stacker crane akan melayani pemindahan material. Dalam hal ini, stacker crane melayani pemindahan bagi lebih dari satu pekerjaan sehingga membutuhkan aturan prioritas yang jelas. Melalui perancangan model simulasi, penelitian ini bertujuan untuk membantu perencana produksi dalam menentukan tiga keputusan penting secara cepat; pengalokasian pekerjaan ke mesin, penentuan jumlah perkakas potong yang harus disediakan di setiap mesin dan penentuan prioritas pemindahan material oleh stacker crane.